(untitled) (AACINI - International Journal of Industrial Engineering, 2022)
The 45% drop in the consumption of sparkling wines (2015 to 2019) after a steady growth of 227% (2000-2015); the increase in the number of sparkling wine houses (61 to 143) and the 27% drop in exports (2012-2019) generated a highly competitive market and decreasing profitability. This pilot study aimed at identifying the prevalent quality cost model in sparkling wine houses and its impact on their profitability. With a case study approach, this exploratory longitudinal research analyzed Bodegas Chandon as the market leader in sparkling wine in Argentina. This study shows the prevalence of the finite quality cost model, which would allow production at 100% product conformity to specifications with a finite quality cost. The analysis also shows a negative correlation between total quality costs and the rate of product conformity to specifications. This indicates that improving each job along the production line and a production process is as valid an option as adopting very costly high technology production lines to reach 100% product conformity to specifications. This approach may improve the financial results of the sparkling wine houses (15% of the winery sector). To date, there is a lack of research on the prevalent quality cost model in the winery sector, and this study fills the gap in the existing literature.